Free Radicals and Extrinsic Skin Aging - Borut Poljšak; Raja Dahmane (Dermatology Research and Practice)
Human skin is constantly directly exposed to the air, solar radiation, environmental pollutants, or other mechanical and chemical insults, which are capable of inducing the generation of free radicals as well as reactive oxygen species (ROS) of our own metabolism. Extrinsic skin damage develops due to several factors: ionizing radiation, severe physical and psychological stress, alcohol intake, poor nutrition, overeating, environmental pollution, and exposure to UV radiation (UVR). It is estimated that among all these environmental factors, UVR contributes up to 80%. UV-induced generation of ROS in the skin develops oxidative stress, when their formation exceeds the antioxidant defence ability of the target cell. The primary mechanism by which UVR initiates molecular responses in human skin is via photochemical generation of ROS mainly formation of superoxide anion (O2−•), hydrogen peroxide (H2O2), hydroxyl radical (OH•), and singlet oxygen (1O2). The only protection of our skin is in its endogenous protection (melanin and enzymatic antioxidants) and antioxidants we consume from the food (vitamin A, C, E, etc.). The most important strategy to reduce the risk of sun UVR damage is to avoid the sun exposure and the use of sunscreens. The next step is the use of exogenous antioxidants orally or by topical application and interventions in preventing oxidative stress and in enhanced DNA repair.